Epidemiological features of COVID-19 family outbreaks in children - Ludmila BIRCA (Asociatia de Biosiguranta si Biosecuritate, 2021)
Introduction. The population of all ages is susceptible to SARS-CoV-2 virus. It is important to determine the role of the child in COVID-19 cases maintenance and spreading. Some research showed that most COVID-19 cases in children were associated with their families.